GE_GERICHTE P/19701/2018 vom 16. Juni 2021 - GE Cour de justice (2021)
IN DUBIO PRO REO;ACTE D'ORDRE SEXUEL SUR UN INCAPABLE DE DISCERNEMENT;SÉJOUR ILLÉGAL;EXPULSION(DROIT PÉNAL) | CPP.10.al3; CP.191; LEI.115.al1.letB; CP.66A.al1